Impact of Workforce Management Digitalization on Operational Efficiency and Accountability in Teaching Factory Units: A Quasi-Experimental Study - Wardani, Dyah Kusuma; Retnowati, Naning; Andini, Paramita; Putra, Mohammad Edwinsyah Yanuan (CV. SPDFHarmony, 2025)
Background: Teaching Factory, TEFA, operations combine learning and real production routines, so workforce management becomes a critical control point for punctuality, documentation quality, and payroll grade reporting. Manual attendance practices commonly create slow recaps, transcription errors, and weak traceability, which can reduce efficiency and trigger disputes. Aims: This study evaluates the short run impact of fingerprint based workforce management digitalization on operational efficiency and accountability in four TEFA units within UPA Pertanian Terpadu at Politeknik Negeri Jember. Methods: A quasi experimental pretest posttest design was applied, comparing four baseline weeks before installation with eight post implementation weeks after stabilization. Four fingerprint devices were installed, synchronized via NTP, and configured for daily CSV export, with SOP governed overrides and role based access control. Indicators were computed from system logs and administrative records, including on time attendance rate, tardiness minutes, effective work hours, missing log rate, SOP override compliance, and weekly recap time. Unit level paired tests were used with two tailed alpha 0.05, complemented by descriptive distributions, reliability checks of a post period perception instrument, and qualitative triangulation. Result: Performance improved consistently after digitalization. On time attendance increased from 66.53 percent to 86.59 percent, tardiness decreased from 14.33 to 7.77 minutes, effective work hours rose from 6.44 to 7.23 hours, missing logs fell from 8.40 percent to 2.58 percent, SOP override compliance increased from 69.28 percent to 92.12 percent, and weekly recap time decreased from 92.50 to 29.46 minutes. Interview and observation evidence aligned with the quantitative pattern, indicating fewer corrections, faster start of shift routines, and more stable recaps. Conclusion: Fingerprint based workforce management digitalization produced substantial improvements in both operational efficiency and accountability in TEFA units by strengthening traceable time stamped records and reducing rework in recap workflows. The findings support institutionalization of log based monitoring and SOP governance, with future studies extending observation windows and linking workforce traceability to downstream TEFA output and quality performance.